2017
DOI: 10.2169/internalmedicine.8578-16
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Lifestyle Factors Associated with Metabolic Syndrome and Preliminary Metabolic Syndrome in the General Population: The Watari Study

Abstract: Objective In Japan, metabolic syndrome (MetS) and preliminary metabolic syndrome (preMetS) are more prevalent in men; however, it remains unclear whether the relationship between these metabolic disorders and lifestyle factors is similar between genders. Methods We examined waist circumference, blood pressure, fasting blood, and various lifestyle factors in 3,166 individuals aged from 30-79 years of age from the Japanese general population. MetS was diagnosed on the basis of central obesity - assessed by waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…In the general population, young people often show less healthy eating habits compared with older generations. 18 20 Of the 929 workers aged 20–40 years in the primary analysis set, 428 (46.1%) regularly ate supper within 2 hours of bedtime, 225 (24.2%) skipped breakfast more than three times a week, and 159 (17.1%) regularly ate snacks after supper; these percentages were higher than for the workers aged ≥40 years (data not shown). Consistent with our data, poor glycemic control and obesity were more frequently reported in younger patients with T2DM.…”
Section: Discussionmentioning
confidence: 93%
“…In the general population, young people often show less healthy eating habits compared with older generations. 18 20 Of the 929 workers aged 20–40 years in the primary analysis set, 428 (46.1%) regularly ate supper within 2 hours of bedtime, 225 (24.2%) skipped breakfast more than three times a week, and 159 (17.1%) regularly ate snacks after supper; these percentages were higher than for the workers aged ≥40 years (data not shown). Consistent with our data, poor glycemic control and obesity were more frequently reported in younger patients with T2DM.…”
Section: Discussionmentioning
confidence: 93%
“…Hattori and colleagues conducted a study on japenesse people, and reported that the prevalence of MetS was significantly higher in male subjects (23.3%) than female subjects (8.7%). 44 Ebrahimi et al reported the prevalence of MetS as 10.88% among males and 13.03% among females. 45 Hajian-Tilaki and colleagues also reported the overall prevalence of MetS as 42.3% (36.5% in males vs. 47.1% in females).…”
Section: Discussionmentioning
confidence: 98%
“…MetS was defined according to the recommendations of the Japanese Committee for the Diagnostic Criteria of Metabolic Syndrome (12,13). The presence of central obesity (WC ≥85 cm in males, ≥90 cm in females) was checked, along with two or more of the following risk factors: lipid abnormality (triglycerides ≥150 mg/dL and/ or HDL cholesterol <40 mg/dL or use of medications for dyslipidemia), high blood pressure (SBP ≥130 mmHg and/or DBP ≥85 mmHg or use of medications for hypertension), and hyperglycemia (fasting blood sugar ≥110 mg/dL or use of medications for diabetes).…”
Section: Definition Of Metsmentioning
confidence: 99%